EFEKTIVITAS PEMBELAJARAN PKN TERHADAP PENGEMBANGAN SIKAP NASIONALISME SISWA DI KABUPATEN MANGGARAI - Yohanes Wendelinus Dasor (PGSD UNIKA SANTU PAULUS RUTENG, 2020)
The purpose of this study was to determine the extent of the effectiveness of PKN learning towards the development of student nationalism in Manggarai Regency. By knowing the effectiveness of PKN learning, the government and educational institutions should specifically pay attention to the whole process of organizing learning. This type of research used in this research is descriptive qualitative conducted in schools from elementary school to high school in Manggarai Regency, East Nusa Tenggara. Data collection techniques in this study were observation and questionnaire. Data analysis techniques include the analysis of student responses and activities. Based on the results of research students in Manggarai Regency have an attitude of nationalism known thanks to the learning PKN obtained during their education. The spirit of student nationalism is reflected in the attitude of creating harmony in religious life, upholding the law, being active in national development and feeling proud as an Indonesian citizen.